The first record of egg masses in tunicates deposited by the snubnose sculpin, Orthonopias triacis, from the Northeastern Pacific: evidence for convergent evolution of an unusual reproductive strategy. Issue 1 (25th October 2021) - Awata, Satoshi; Ito, Takeshi; Crow, Karen D.; Koya, Yasunori; Munehara, Hiroyuki
Abstract: In this study, the authors report the first record of egg masses deposited in solitary tunicates by the snubnose sculpin, Orthonopias triacis, from the Northeastern Pacific. Four egg masses were discovered in the tunicate Ascidia ceratodes that were genetically determined to be O. triacis . Female O. triacis had long ovipositors that allow deposition of their eggs inside the atrium of the tunicates. A comparison of host‐tunicate size with ovipositor length of sculpins from the Northwestern Pacific, including the genera Furcina and Pseudoblennius, revealed that O. triacis had shorter ovipositors and spawned in the atrium of smaller species of tunicates. Ancestral state reconstruction of egg deposition in solitary tunicates using 1.86Mbp RNAseq data of 20 sculpin species from Northeastern and Northwestern Pacific revealed that this unusual spawning behaviour may have evolved convergently in different species occurring in the Northeastern vs . the Northwestern Pacific.